1996
DOI: 10.1074/jbc.271.46.28805
|View full text |Cite
|
Sign up to set email alerts
|

Resonance Raman Spectra of Native and Mesoheme-reconstituted Horseradish Peroxidase and Their Catalytic Intermediates

Abstract: Resonance Raman studies of native and mesohemereconstituted horseradish peroxidase and their catalytic intermediates, known as Compounds I and II, have been conducted using both near UV (ϳ350 nm) and visible (406.7 nm) excitation. Careful power studies indicate that the authentic Compound I spectra are obtainable using near UV excitation, but that use of visible excitation results in contamination of the Compound I spectrum with the spectrum of a Compound II-like photoproduct. Using H 2 18 O 2 , the (Fe‫؍‬O) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
44
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 41 publications
4
44
0
Order By: Relevance
“…The extended x-ray absorption fine structure and resonance Raman data reported for these systems are in good agreement with Badger's rule (6,(11)(12)(13)(16)(17)(18)(19), whereas the crystallographically determined bond distances deviate from it substantially (7-9). The long Fe-O bonds that have been reported in the crystal structures of these enzymes appear to be the hallmarks of ferric and ferrous hydroxides (14).…”
Section: Ron(iv)-hydroxides Have Been Implicated In the Catalyticsupporting
confidence: 71%
“…The extended x-ray absorption fine structure and resonance Raman data reported for these systems are in good agreement with Badger's rule (6,(11)(12)(13)(16)(17)(18)(19), whereas the crystallographically determined bond distances deviate from it substantially (7-9). The long Fe-O bonds that have been reported in the crystal structures of these enzymes appear to be the hallmarks of ferric and ferrous hydroxides (14).…”
Section: Ron(iv)-hydroxides Have Been Implicated In the Catalyticsupporting
confidence: 71%
“…Since 2 , which primarily involves C b -C b stretching, is coupled with vinyl CϭC stretching (41,42), removal of the vinyl group leads to an increase in the frequency of 2 due to decoupling of the 2 and vinyl stretching modes (41)(42)(43). In fact, horseradish peroxidase reconstituted with mesoheme, which has ethyl groups instead of vinyl groups in the 2-and 4-positions of heme, showed an upshifted 2 at 1582 cm Ϫ1 as compared with that observed at 1573 cm Ϫ1 for native horseradish peroxidase (44). Previous studies have shown that the 2-vinyl mode has a more significant effect on the 2 frequency than the 4-vinyl (45).…”
mentioning
confidence: 95%
“…The Compound I species of CPO and HRP have sufficient half-lives for resonance Raman and EPR studies and have been well characterized (3,5,(15)(16)(17). The same peroxy acid and its derivatives have been used with P450s in attempts to generate intermediates.…”
mentioning
confidence: 99%